Temporal Changes in Indicators of Testicular Dysgenesis Syndrome in Labrador and Golden Retrievers - Thomas Lewis; Rachel Moxon; Gary C. W. England (Animals)
Temporal changes in testicular traits have been reported in both humans and dogs. Analysis of % living sperm and motility from semen collections from 186 Labrador Retrievers and 113 Golden Retrievers between 2006 and 2023, and of incidents of cryptorchidism in over 15,000 dogs of the same breeds and crosses born between 1994 and 2023 was undertaken to determine influential factors. A general temporal increase in incidence of cryptorchidism masked significant differences in the trend between breeds, which persisted after accounting for genetic and litter effects. The incidence in the F1 cross was significantly lower than in either pure breed, implying hybrid vigour. The semen traits were both moderately repeatable within individuals, but this belied breed differences in its composition; for both traits, only the heritability was significantly greater than zero in the Golden Retriever, while only the permanent environment effect was present in Labrador Retrievers. There were significant negative temporal trends in Golden Retrievers for both semen traits, but not in Labrador Retrievers; significant negative effects of age (except on % motility in Labrador Retrievers); and significant negative effects of a diagnosis of benign prostatic hyperplasia on both traits in both breeds. These results reveal complex breed by environment interactions in traits related to testicular form and function.